An implementing of zigzag pattern in numbering watermarking bits for high detection accuracy of tampers in document - Usop, Nur Alya Afikah; Izhar Hisham, Syifak; Abd Ghani, Aqilah; Mohd Zain, Jasni (Engg Journals Publications, 2022)
Digital form nowadays has been easily manipulated by many corrupters especially in formal business. PDF document is one of the main digital forms that need to be accessed when dealing with offer letters, scanned documents, digital receipt, etc. Thus, PDF is one of the critical data that needs to be protected from any manipulations of its originality. An experiment is conducted to develop an improved zigzag-LSB watermarking scheme for all characters of text documents in PDF format which proved to have the best embedding system of numbering. The techniques used special numbering manners by spreading the numbered original data as far as possible from the original locations. The schemes embedded authentication data in least significant bits (LSB). These methods have been proven to be effective since it uses an image-based approach with a numbering pattern that is robust to deletion, image splicing, and copy attacks. Results show three types of attacks in PDF documentation managed to detect tamper location after being tampered.